Opportunity and Equity: Fixing Maine’s School Funding Formula - Breen, Yellow (Maine Policy Review, 1999)
In its last session, the legislature adopted much needed reforms to Maine’s education funding formula. Among other things, these reforms help to establish a link between education funding and student performance, to recognize the true costs of education, and to better measure the communities’ relative ability to pay. Yellow Light Breen explains each of these elements to be phased in over the next several years. He also responds to Peter Mills’ argument (this issue) to eliminate income from the definition of ability to pay and on the need for broader changes in how local government is funded. He notes that the recently adopted reforms allow policymakers the necessary breathing room to tackle these broader issues, but cautions legislators to stay the course in completing the reforms they just enacted.
Keywords: Maine school funding